2023
DOI: 10.1111/obr.13540
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity prevention for and with adolescents: The “Confronting obesity: Co‐creating policy with youth” (CO‐CREATE) project

Abstract: The CO-CREATE project focuses on the need for research on obesity prevention in adolescents to move away from studies of single interventions, toward the investigation of systems-based research incorporating youth involvement. This paper provides an overview of the project, presenting the objectives, design, and novel methodologies applied, as well as findings to date and anticipated outcomes. Adolescents (16-18 years old) in five European countries participated. Methods applied in the project include monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 22 publications
(48 reference statements)
0
43
0
Order By: Relevance
“…Adolescents from five countries (the Netherlands, Norway, Poland, Portugal, and the United Kingdom) who were part of alliances involved in the CO‐CREATE youth alliance activities 4 were invited to complete an online baseline questionnaire in 2019 or 2020. The questionnaire was sent to participants' e‐mail addresses or cell phone numbers and it took approximately 10–15 min to complete.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescents from five countries (the Netherlands, Norway, Poland, Portugal, and the United Kingdom) who were part of alliances involved in the CO‐CREATE youth alliance activities 4 were invited to complete an online baseline questionnaire in 2019 or 2020. The questionnaire was sent to participants' e‐mail addresses or cell phone numbers and it took approximately 10–15 min to complete.…”
Section: Methodsmentioning
confidence: 99%
“…3 In the Confronting obesity: Co-creating policy with youth project (CO-CREATE), which aims to reduce the prevalence of obesity among adolescents in Europe through policy actions to promote a healthier food and physical activity environment, adolescents have not merely been the object of the intervention but have themselves been agents for change by identifying required actions and collaborating to achieve them. 4 The adolescents were involved in participatory action research, 5 which has been found to be an effective tool for young people to address inequalities in various social issues, including health, as well as for promoting civic and political engagement. 6,7 Although increasing attention is paid to youth involvement and empowerment, there is a dearth of developed and validated measures that can be used to assess adolescents' readiness to engage in action to address obesity and in other intermediary outcomes or process measures within the field of obesity prevention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principles of PAR include “a cooperative, iterative process of research and action in which non‐professional community members are trained as researchers and change agents, and power over decisions are shared among the partners in the collaboration.” 29 Furthermore, “[PAR] focuses on research whose purpose is to enable action. Action is achieved through a reflective cycle, whereby participants collect and analyse data, then determine what action should follow.” 22 An essential element of PAR is “the transfer of knowledge, particularly the technical skills transferred from researcher to community partners.” 30 PAR principles thus include a phase of empowerment in which participants are provided with capacity building through training or facilitation to further enable them to understand their own lived situation and make use of their situated knowledge.…”
Section: Youth‐led Participatory Action Researchmentioning
confidence: 99%
“…This protocol has been written as part of the Co-Create project, which is an ongoing research project funded by the European Commission that involve youth in five European countries and South Africa in the development of policy ideas relating to obesity prevention. 14 The results of this scoping review will provide new insights on how to involve youth in policy processes and its effects in public health, education, and social work, including relating to obesity prevention. This will have the potential to guide future research, policy processes, and advocacy work.…”
Section: Why Is It Important To Do This Review?mentioning
confidence: 99%